Application of a novel and simple TEST to evaluate the corrosion resistance of magnesia-based refractories to sulfur gases. Issue 16 (November 2020) - Fonseca, Daniela M.; Gregurek, Dean; Nunes, Eduardo H.M.
Abstract: In this work, a novel and simple test to evaluate the chemical resistance of basic refractories to sulfur gases is introduced. This test is based on the measurement of apparent porosity and bulk density of MgO-based samples before and after heat treatment in a SO2 /SO3 -rich atmosphere. It was demonstrated that the larger the variation in these properties, the lower the corrosion resistance of the refractory. This method was used to investigate the influence of the CaO to SiO2 (C/S) ratio on the chemical resistance and physical properties of refractory bricks. Samples with C/S ratios below 0.5 showed higher corrosion resistance due to the presence of forsterite (Mg2 SiO4 ) as the primary interstitial phase, which does not react with the sulfur gases to form magnesium and calcium sulfates. The generation of such phases may cause the blocking of the pore structure and decrease the mechanical strength of the refractory lining.